1984
DOI: 10.1177/014860718400800103
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid and Total Parenteral Nutrition

Abstract: The stability of folic acid in a variety of solutions used for parenteral nutrition has been determined over a 2-wk period. Provided that the acidity of the solution remains above pH 5.0 the folate, in the concentrations usually used for parenteral nutrition, will remain stable in solution, and all of the folate added to the solution will be delivered to the patient. The applicability of this in vitro work to a group of patients requiring parenteral nutrition was assessed, in order to determine a suitable dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Optimal p H stability seems to be around 7, but the values found in the literature vary (32). If a solution has a p H lower than 5.0, folic acid may precipitate ( 19).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal p H stability seems to be around 7, but the values found in the literature vary (32). If a solution has a p H lower than 5.0, folic acid may precipitate ( 19).…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…Thiamine is stable in some amino acid solutions (lo), but may degrade in the presence of bisulphite (16,17). When mixed with parenteral nutrition solutions the availability of folic acid may be impaired (18,19). Ascorbic acid is stable in some parenteral nutrition solutions (171, while it is shown to degrade in solutions containing trace elements (1 0,15).…”
mentioning
confidence: 99%
“…There has been a suggestion by Lee et al 49 that adsorption of folic acid onto polyvinylchloride (PVC) infusion bags may occur and was responsible for a 33% loss seen after 42 days of storage. However, later studies have found the vitamin to be compatible with PN bags 11,48 .…”
Section: Folic Acidmentioning
confidence: 98%
“…Folic acid injections are usually formulated at a pH in excess of 8.0 because the vitamin is prone to precipitation at lower pHs 47 . One investigation examined the effect of pH on folic acid precipitation and found that if the pH remains above 5.0, folic acid remains in solution 48 . As PN usually has a pH of between 5.0-6.0, folic acid should not precipitate.…”
Section: Folic Acidmentioning
confidence: 99%
“…After addition to T P N mixtures, there is a danger of free folate precipitation. Barker et al (54) have recently reported that folic acid is stable and remains in solution in T P N mixtures provided the pH remains above 5.0. Folic acid may be added to Synthamin or Freamine 11-containing mixtures which can be stored at 2 4 C for 14 days without any evidence of precipitation.…”
Section: Folic Acidmentioning
confidence: 99%